2014
DOI: 10.1007/s00436-014-3846-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the expression of cytoskeletal proteins of Taenia crassiceps ORF strain cysticerci (Cestoda)

Abstract: The Taenia crassiceps ORF strain is used to generate a murine model of cysticercosis, which is used for diagnosis, evaluation of drugs, and vaccination. This particular strain only exists as cysticerci, is easily maintained under in vivo and in vitro conditions, and offers an excellent model for studying the cytoskeletons of cestodes. In this study, several experimental approaches were used to determine the tissue expression of its cytoskeletal proteins. The techniques used were microscopy (video, confocal, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…In the present study, changes in the fluorescence of polymerized actin or tubulin were observed in cysticerci tissues following FCF treatment (Supplementary Figure 7). These gross observations may indicate that FCF-induced alterations in SEPT4_Tsm disrupt the polymerization of actin and tubulin in T. crassiceps cysticerci, as we have previously shown [20]. Future studies on the interactions between septins and these cytoskeletal proteins should demonstrate the exact nature of this relationship and its importance for the survival of cysticerci.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…In the present study, changes in the fluorescence of polymerized actin or tubulin were observed in cysticerci tissues following FCF treatment (Supplementary Figure 7). These gross observations may indicate that FCF-induced alterations in SEPT4_Tsm disrupt the polymerization of actin and tubulin in T. crassiceps cysticerci, as we have previously shown [20]. Future studies on the interactions between septins and these cytoskeletal proteins should demonstrate the exact nature of this relationship and its importance for the survival of cysticerci.…”
Section: Discussionsupporting
confidence: 63%
“…Then, cysticerci were fixed with 4% paraformaldehyde and observed under a microscope at 20× magnification (Diaphot; Nikon, Chiyoda-ku, Tokyo, Japan) equipped with an epifluorescence accessory and the appropriate filters. The indirect effects of FCF over actin and α -tubulin of T. crassiceps cysticerci were evaluated in cryosections with phalloidin–rhodamine and commercial DM1A antibody as described in other studies performed by us [20, 22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss-of function unc-89 mutants display disorganized myosin thick filaments and reduced motility [58]. Besides, myosin-2 is mainly expressed at muscle fibrils in the parasite tegument and the function is to provide motile force through ATP hydrolysis [59]. Therefore, inhibition of myosin-2 or UNC-89 in parasites results in rapid declines in motility, which are in agreement with our previous observations that bath treatment with ARG resulted in rapid declines of G. kobayashii motility [24].…”
Section: Discussionmentioning
confidence: 99%